Anomalous 14C Enrichments in the Eastern UK Coastal Environment. Issue 3 (2015) - Muir, Graham K P; Cook, Gordon T; MacKenzie, Angus B; MacKinnon, Gillian; Gulliver, Pauline
Abstract : During the period from 1995 to 2011, radiocarbon measurements from the coast around Hartlepool in NE England have revealed anomalous enrichments in seawater, sediment, and marine biota. These cannot be explained on the basis of atomic weapons testing or authorized nuclear industry discharges, including those from the nearby advanced gas-cooled reactor. Enhanced 14 C-specific activities have also been observed since 2005 in biota during routine monitoring at Hartlepool by the Food Standards Agency, but are reported as "likely" originating from a "nearby non-nuclear source." Studies undertaken in Hartlepool and Teesmouth during 2005 and 2011 suggest that the 14 C discharges are in the vicinity of Greatham Creek, with activity levels in biota analogous to those measured at Sellafield, which discharges TBq activities of 14 C per annum. However, if the discharges are into Greatham Creek or even the River Tees, it is proposed that they would be much smaller than those at Sellafield and the high specific activities would be due to much smaller dilution factors. The discharge form of the 14 C remains unclear. The activity patterns in biota are similar to those at Sellafield, suggesting that initial inputs are dissolved inorganic carbon (DI 14 C). However, the mussel/seaweed ratios are more akin to those found around Amersham International, Cardiff, which is known to discharge 14 C in an organic form. 14 C analysis of a sediment core from Seal Sands demonstrated excess 14 C to the base of the core (43–44 cm). 210 Pb dating of the core (0–32 cm) produced an accumulation rate of 0.7 g cm −2 yr −1, implying that 14 C discharges have occurred from the 1960s until the present day.